Activity Time Budget of Asian Elephants (Elephas maximus L.) in Idukki Wildlife Sanctuary, Kerala, South India - Vinod, T. R.; Cheeran, Jacob V. (Indian Forester, 1997)
The present study on the activity time budget of Asian Elephants (Elephas maximus Linn.) was carried out in Idukki Wildlife Sanctuary, Kerala during 1993-94. Feeding accounted for 65.45% of the activity in dry season and 8O.77% in wet season. Drinking was found to vary from 2.73% of the activity in dry season to 1.92% in wet season. There was a significant seasonal difference in time spent on feeding whereas it was found to be non-significant for drinking. Grazing was predominant in both dry (63.89%) and wet (71.43%) seasons, indicating the importance of grasslands for the conservation of the species.